2020
DOI: 10.2147/opth.s263474
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reduction of Intraocular Pressure Spikes Due to Intravitreal Bevacizumab Injections by Scleral Indentation with Cotton Swab or Digital Ocular Massage: Innovative Techniques Compared</p>

Abstract: This study aims to evaluate the effectiveness of different decompressive injection techniques in reducing intraocular pressure (IOP) spikes, if compared to the injection without pressure applied on the eye, following the intravitreal injection of bevacizumab. Patients and Methods: Two hundred patients with indication to intravitreal therapy were randomized into five arms: 40 received intravitreal injection without ocular decompression (arm A), 40 with pre-injection scleral indentation with cotton swab (arm B),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…7,16 Second, performing intraocular decompression with a cotton tip applicator prior to intravitreal injection may be considered to reduce the incidence of an IOP spike following J o u r n a l P r e -p r o o f injection, though this method has yet to be validated for pre-filled syringes in larger prospective studies. [17][18][19] Third, we recommend injecting at a slower rate. Our data demonstrate that injection speed is directly proportional to injection force; decreasing injection speed by adding an extra second may result in significantly lower injection forces.…”
Section: Discussionmentioning
confidence: 99%
“…7,16 Second, performing intraocular decompression with a cotton tip applicator prior to intravitreal injection may be considered to reduce the incidence of an IOP spike following J o u r n a l P r e -p r o o f injection, though this method has yet to be validated for pre-filled syringes in larger prospective studies. [17][18][19] Third, we recommend injecting at a slower rate. Our data demonstrate that injection speed is directly proportional to injection force; decreasing injection speed by adding an extra second may result in significantly lower injection forces.…”
Section: Discussionmentioning
confidence: 99%
“…Some suggested that the inflammation in trabecular area causes direct raise in IOP (19). Some postulated direct damage to trabecular meshwork after multiple injection (20). On the other hand, there is also possibly of ranibizumab (48-kilodalton (kDa)) accumulated in trabecula and schlemm's canal causing direct or indirect obstruction of the outflow (19).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some innovative manipulations such as scleral indentation with cotton swab and ocular digital massage pre-and post-procedure significantly reduces the excessive rise of IOP post intravitreal injection (20). The mechanism of this maneuver is yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“… 46 Hence, improvement of the IVI technique and perfection of the required instrumentation remain the focus of numerous studies aimed to reduce the rate of complications. 47–51 Since the last decade, a number of different devices for IVI were proposed and introduced into clinical practice. Among the main issues which hypothetically could reduce the complication rates associated with IVIs are the stability of the eye, enhanced sterility of the injected area, diameter of the needle and premeasured distance from the limbus, which are all required for safe procedures.…”
Section: Discussionmentioning
confidence: 99%